Implementation of Student Management in Strengthening Students' Religious Character Values - Devita Amelia Jamil; Moh Rofiki (Prodi PGMI STIT Sunan Giri Bima, 2026)
Strengthening religious character among students is one of the important goals of Islamic education and requires strong student management. This study aims to describe the implementation of student management to strengthen students' religious character values at MTs Mambaul Ulum Al-Murtadlo. This research uses a qualitative, case-study approach. Data were obtained through observation, interviews, and documentation, then analysed using data reduction techniques, data presentation, and conclusion drawing. The research results show that strengthening students' religious character values is achieved through the planning, implementation, and evaluation of religious-based student programs. At the planning stage, the madrasah organises various religious activities that align with the school's vision and goals. The program is implemented regularly through activities such as congregational prayers, Quran recitation, istighotsah, and moral development, involving all school members. Evaluation is conducted periodically to monitor the development of student behaviour and as a basis for program improvement. The implementation of student management strengthens students' religious character values, as evidenced by increased discipline, responsibility, adherence to regulations, and the habit of carrying out religious activities in daily life.